Wildland Fuel Fundamentals and Applications - Keane, Robert E. (Springer International Publishing : Imprint: Springer, 2015)
Wildland fuels are a critical factor in fire management because they are the one factor that managers can control.  However, fuels have always been defined, described, and quantified in the context of inputs to fire behavior models.  Wildland fuel science was always considered part of fire behavior research and the two have been intimately linked for over 50 years.  Now, however, there are many other critical applications for wildland fuels, such as carbon accounting, wildlife habitat assessment, erosion control, and smoke calculation. The rigid fire behavior treatment of fuels does not lend itself to these other important fields.   Wildland Fuel Fundamentals and Application is the first book to highlight wildland fuels and treat them as a natural resource rather than just a fire behavior input. This volume serves as a synthesis of fuels information in the context of ecology that can be used to understand basic fuels characteristics to objectively evaluate results of fire research and management applications. It is the only volume to provide a comprehensive description of fuels as well their ecology and measurement in one place.